Comparative Efficacy and Safety of Phosphate Binders in Hyperphosphatemia Patients With Chronic Kidney Disease. Issue 4 (19th December 2017) - Yang, Xiuqin; Bai, Qingning; Li, Yanguo; Liu, Haijun; Guo, Haiying; Zhang, Xiaolei
Abstract: Background : In this study, we coordinated a network meta‐analysis to establish the efficacy and safety of different agents used in the treatment of hyperphosphatemia patients with chronic kidney disease. Methods : PubMed, CNKI, and Embase were systematically searched to retrieve relevant studies. Outcomes were presented by mean differences, odds ratios, and corresponding 95% credible intervals for continuous outcomes and binary outcomes, respectively. Each therapy was ranked according to the value of surface under the cumulative ranking curve. Consistencies between direct and indirect comparisons were assessed with a node‐splitting plot. Results : In terms of efficacy end points (including levels of serum phosphate, serum calcium, serum intact parathyroid hormone, and serum calcium × phosphorus product), all 7 kinds of agents outperformed or performed at least equally to placebo, with iron‐based phosphate‐binding agents being potentially the most effective. As for safety end points (including mortality, adverse events, and all‐cause discontinuation), almost all agents were equivalent in term of mortality and all‐cause discontinuation except in the comparison between iron‐based phosphate‐binding agents and placebo. Meanwhile, iron‐based phosphate‐binding agents colestilan and nicotinic acid performed poorly compared with placebo in terms of adverse events. Furthermore, iron‐based phosphate‐binding agents were potentially the safest agents followed sequentially by calcium‐based phosphate‐binding agents and placebo. Conclusion : Iron‐based phosphate‐binding agents were the preferable agents when considering efficacy and safety simultaneously.